Cultural work provisions in the Zionist organization «Gekholuts» program documents - I. Yu. Berezhanskaya (Омский научный вестник: Серия "Общество. История. Современность")
The Zionist movement idea did not leave indifferent representatives of the Jews in the Russian Empire. In connection with the repeal of restrictive laws after February 1917, the political activity of the Jewish population increased significantly. However, October 1917 changed the direction of the Zionist movement, as the new government gradually began to persecute members of the parties and organizations that existed at that time, declaring them counter-revolutionary and anti-Soviet. At that time, the Zionist movement was already a political force with programmatic documents, statutes, educational literature, printing presses. One of the issues that occupied her mind was the question of educational and cultural work in the ranks of the Zionist movement. One of the organizations that prepared young people for a new life in the new state was «Gekholuts». Program documents covering the main points of her work in Soviet Russia have been preserved in Russian archives and partially published. They contain information about what kind of cultural work should be carried out with young adherents of the Zionist idea in building a future Jewish state. By 1930, the Soviets had eradicated the Zionist movement, and its followers moved to Palestine whenever possible to implement their ideas, particularly on the importance of cultural work, there.